Effect of Moisture Gradient on the Growth and Nutrient Uptake of Sal (Shorea robusta) Seedlings - Seth, S. K.; Srivastava, P. B. L. (Indian Forester, 1971)
Insufficient availability of moisture during the critical period of growth of sal seedlings is considered to be by far the most important factor inhibiting natural regeneration especially in the dry types of sal. However, experimental data on the actual moisture requirements of this species is lacking. The present article describes the results of an investigation wherein optimum moisture range and its affect on nutrient uptake for the growth of sal seedlings were studied with the help of an especially designed apparatus. The results indicate that in loamy soils, sal seedlings on an average require moisture to the extent of 85% of water holding capacity and 12% more than the moisture equivalent for optimum growth and there is an appreciable reduction in height increment below and above this range. Plants growing within the optimum range also absorbed greater amounts of nutrients especially Calcium, Magnesium and Phosphorus. The analysis of the residual soils indicates that the transfer of nutrients in the soil matrix is a slow process and a local deficiency may develop in the rooting zone which is not compensated by the diffusion of nutrients from neighbouring soil regions.